Vpliv barve embalaže čokolade na zaznavanje okusa in teksture čokolade - Grah, Miran (Akademija MM, 2015)
This article examines the impact of packaging colour (red, blue, violet) on the perception of taste (sweet-bitter) and textures (hardsoft, soluble-insoluble) of chocolate. Presented are the results of the associations of key stimulus chocolate, the results of the content analysis of interviews with a focus group and results of the experiment carried out on a sample of 188 persons. We have concluded that colours of the packaging affect the perception of taste and texture of chocolate. Statistically significant differences exist in the perception of taste of chocolate on the dimension sweet-bitter between red and violet colour of packaging. Between perception of taste of chocolate in red and blue packaging and violet and blue packaging there are no statistically significant differences. There is also a difference in the perception of solubility of chocolate. Statistically significant differences in perception of solubility of chocolate exist between red and violet colours of packaging of chocolate and red and blue colours of packaging of chocolate. There is no statistically significant difference in perception of solubility of chocolate in violet and blue packaging. The most intensive influence appeared in the third dimension of chocolate perception labeled as hard-soft. In this case statistically significant differences were found in the perception of chocolate between all three colours of chocolate packaging.
Keywords: čokolada; embalaža; okus; proizvodi; vplivi